Respuesta :

Answer:

-11

Step-by-step explanation:

Given :

[tex]f(x) = -\frac{3}{8} \left(24-\frac{32}{x}\right) -x[/tex]

We have to find f ( - 2 ):

Putting x = - 2 in f ( x ) we get :

[tex]f(-2) = -\frac{3}{8} \left(24-\frac{32}{-2}\right) -(-2)\\[/tex]

[tex]\implies f(-2) = -\frac{3}{8} \left(24-( -16)\right) +4 \\[/tex]

[tex]\implies f(-2) = -\frac{3}{8} \left(40\right) +4 \\[/tex]

[tex]\implies f(-2) = -3\times \left(5\right) +4[/tex]

[tex]\implies f(-2) = -15 +4[/tex]

[tex]\implies f(-2) = -11[/tex]

Therefore value of f ( - 2 ) is - 11.

9514 1404 393

Answer:

  -13

Step-by-step explanation:

Put -2 where x is and do the arithmetic.

  [tex]f(x)=-\dfrac{3}{8}\left(24-\dfrac{32}{x}\right)-x\qquad\text{given}\\\\f(-2)=-\dfrac{3}{8}\left(24-\dfrac{32}{-2}\right)-(-2)=-\dfrac{3}{8}(24+16)+2\\\\f(-2)=-15+2=\boxed{-13}[/tex]

Ver imagen sqdancefan